Posted by jason on Friday, February 15, 2008 at 12:23am.
C be Cathy's age now and B be Byte's age now.
B+4 = (3/4) (C+4) = (3/4) C + 3
B-4 = (1/2) (C-4) = (1/2) C - 2
Subtract the two equations (left and right sides separately)
8 = (1/4) C + 5
C/4 = 3
C = 12
Use either of the first equations to get B.
in B+4 = (3/4) (C+4) = (3/4) C + 3
B-4 = (1/2) (C-4) = (1/2) C - 2
may I ask where you got the +3 and -2?
the +3 comes from...
(3/4)*(c+4)
which is another way of saying
((3/4)*c)+(3/4*4)
or
3/4C+(12/4)
3/4C+3
The -2 comes from multiplying 1/2 *(c-4) which is 1/2C-4/2 or simply 1/2c-2
the +3 comes from...
(3/4)*(c+4)
which is another way of saying
((3/4)*c)+(3/4*4)
or
3/4C+(12/4)
3/4C+3
The -2 comes from multiplying 1/2 *(c-4) which is 1/2C-4/2 or simply 1/2c-2
these questions become easy if you organize your data in a chart form
------------Byte-----Cathy
Age now ---- b ------ c
in 4 yrs -- b+4 ---- c+4
4 yrs ago-- b-4 ---- c-4
so from second line: b+4 = 3/4(c+4)
from third line: b-4 = 1/2(c-4)
These two equations are now easy to simplify and solve giving you the answer provided by drwls above
BUTTCHEEKS!!!!!!!